(untitled) (Journal of Biomedical Investigation, 2009)
Bakers yeast was isolated, characterized, and propagated from local palmwine Elaeis guinensis, collected from two different stations, namely: Mgbakwu, in Awka North Local Government Area and Nchagbo, in Ihiala Local Government Area, both in Anambra State. This was carried out with the aid of Saubraud Dextrose Agar (SDA), using a Pour Plate Technique (PPT). The inoculation was carried out and incubated for three days at room temperature. The mixed yeast colonies obtained at the end of the incubation period were purified into pure cultures by sub-culturing into a fresh SDA, using Streaking Plate Technology (SPT). The characterization of yeast was carried out on the basis of the cultural, microscopic and biochemical examination of the isolates of yeast. The yeast finally isolated, characterized and identified include: Saccharomyces cerevisiae, Schizosaccharomyce pombe and Saccharomyces exigus. Pure cultures of S. cerevisiae were propagated and multiplied using cane molasses to obtain a good deal of biomass.